Consumer Behavior in Watching the Korean Series "Moving" on Korean Series Facebook Fan Pages - Tadaamnuaychai, Montira (Siam Communication Review, 2025)
In this study, the Facebook fan page “1 day with series” will be used to determine the content and presentation technique of the review content of the Korean series "Moving." his study focused on wall-posted information through the application of narrative and user generated content concepts to study findings. Facebook content from June 29 to September 21, 2023 was included in the unit of analysis. The study also found that there were 11 content review types as follows: content that mentioned on characters of main characters, special abilities of characters, content that mentioned relationships of lovers in series, content that mentioned all main characters, content that summarized all episodes, content that portrayed love and romanticized of characters, content that portrayed woman power, conversation content between mother and son, mission content in series, content provided series information, content of 1st ranking of Disney+ in worldwide and behind the scene content.